Debt Policy On Profit Management In Advertising, Printing Subsector Companies Listed On The Indonesia Stock Exchange In 2018-2021: - Nadya Salsabila Z; Seflidiana Roza; Nurhayati (ProBisnis : Jurnal Manajemen, 2023)
This study aims to analyze the Effect of Share Ownership and Debt Policy on Profit Management in Advertising. Printing and Equipment Subsector Companies with a sample of 13 Advertising. Printing and Equipment Companies Listed on the Indonesia Stock Exchange using the Purposive Sampling method for the 2018-2021 period. Based on the results of statistical analysis, it can be concluded that share ownership has a significant effect on earnings management in the companies studied This is mdicated by the results of the t-test, tcount -2 608 ttable1.677, a significance of 0.12 of 0.05 So it can be concluded that share ownership affects earnings management. Based on the results of statistical analysis, it can be concluded that Debt Policy has no significant effect on Earnings Management in the companies studied. This is indicated by the results of the tcount -1.582 ttable 1677 and a significance of 0.120 from a significance level of 0.05. So it can be concluded that the debt policy variable has no effect on earnings management Significantly, share ownership and debt policy have a significant effect on earnings management. This is proven by using the F test with a significance value of 0.020-0.05 and fcount 4.226 ftable 3.187. This can be seen from the R Square value of 14.7 or 14.7% and is influenced by other variables that have not been studied at 85.3%   Keywords: Share Ownership, Debt Policy, Earnings Management.